No margins: Writing Canadian fiction in lesbian - Lake, Catherine; Holtz, Nairne (Insomniac Press, 2006)
Elegant tomboys, academic femmes, small town kisses, and international dykes; road trip encounters and scenes from a straight bar; questions arising from an in-between culture; the music of travel and hotel room orgasms. Crossing race, culture, and gender constraints, No Margins leads the reader through the lushness of lesbian life and the vastness of Canadian experience.No Margins is a stellar short fiction collection featuring fifteen of Canada's finest contemporary writers, all of whom include lesbian identity as a piece of their selves and their work. These highly acclaimed authors were selected to convey the places we currently inhabit and the future we are forging. The contributors have included notes to accompany their work, thus sharing the creative process and speaking on the politics of lesbian writing. No Margins is an unprecedented anthology, reflecting an esteemed gathering of women who are currently shaping Canadian literature.Featuring the work of: Luanne Armstrong • Dionne Brand • Nicole Brossard • Emma Donoghue • Marion Douglas • Anne Fleming • Jane Eaton Hamilton • Lydia Kwa • Larissa Lai • Ann-Marie MacDonald • Daphne Marlatt • Shani Mootoo • Elizabeth Ruth • Karen X. Tulchinsky • Marnie Woodrow
Keywords: amériques; anthologie; canada; fiction; littérature; outils; ouvrages de références; personnes lesbiennes; ressource en ligne; régions géographiques